2017
DOI: 10.1093/jtm/tax033
|View full text |Cite
|
Sign up to set email alerts
|

Single visit rabies pre-exposure priming induces a robust anamnestic antibody response after simulated post-exposure vaccination: results of a dose-finding study

Abstract: This dose finding study demonstrates that priming with a single dose of rabies vaccine was sufficient to induce an adequate anamnestic antibody response to rabies PEP in all subjects 1 year later, even in those in whom the RVNA threshold of 0.5 IU/ml was not reached after priming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 27 publications
2
35
0
1
Order By: Relevance
“…There were 11 citations identified that reported immunogenicity data following ID PVRV for PrEP [16,[20][21][22][23][24][25][26][27][28][29]; of these, 6 were undertaken in Thailand [20,23,25,[28][29][30]. The other studies were undertaken in Vietnam [24,27] (both these Vietnamese studies reported data on the same cohort of children), Brazil [22], and The Netherlands [16,21].…”
Section: Immunogenicity Of Prep Regimensmentioning
confidence: 99%
See 4 more Smart Citations
“…There were 11 citations identified that reported immunogenicity data following ID PVRV for PrEP [16,[20][21][22][23][24][25][26][27][28][29]; of these, 6 were undertaken in Thailand [20,23,25,[28][29][30]. The other studies were undertaken in Vietnam [24,27] (both these Vietnamese studies reported data on the same cohort of children), Brazil [22], and The Netherlands [16,21].…”
Section: Immunogenicity Of Prep Regimensmentioning
confidence: 99%
“…Seroconversion rates from day 14 to 56 after the first vaccination and at 1 year across the studies identified were 90-100% and 20-96%, respectively [16,[21][22][23]25,[27][28][29]. The RVNA GMTs reported across the studies irrespective of PrEP regimen (n = 926), including following booster vaccination after one year, are summarized in Figure 2 [16,[20][21][22][23][24][25][26][27][28][29].…”
Section: Immunogenicity Up To 1 Yearmentioning
confidence: 99%
See 3 more Smart Citations